Intergenerational Synchrony and Its Effect on Bonding and Group Closeness among Young and Older Adults - Assaf Suberry; Ehud Bodner (Behavioral Sciences, 2024)
To examine the effect of synchronous dance movements on social bonding and perceived closeness between generations, 168 young (20–45 years) and older (65–90 years) participants were randomly assigned to six dyad conditions. These included dancing synchronously or asynchronously with an in-age-group or out-age-group unfamiliar partner for 11 min. The participants then completed social bonding and group closeness questionnaires. To assess variation across individuals’ and dyads’ measurements, a generalized estimating equation modeling analysis was conducted. In line with the hypotheses, synchronized dancing increased social bonding, and young adults showed an enhanced perception of closeness between generations. The hypothesis that synchronous dancing with out-age-group members would foster greater perceived closeness compared to in-age-group members was not confirmed. Surprisingly, the results indicated that asynchronous movements with the in-age-group led to a higher degree of closeness between generations than asynchronous movements with the out-age-group. Avenues for future studies on the mechanisms by which intergenerational dance fosters intergenerational bonding and closeness are discussed.